Students'perception on the implementation of the marketing strategies by private colleges in Polokwane Local Municipality, Limpopo Province, South Africa - Giliana, Freedom (My University, 2025)
This study investigates students' perceptions on the marketing strategies implemented by private colleges in Polokwane, Limpopo Province, South Africa. As competition in the higher education sector intensifies, private colleges must adopt effective marketing strategies to attract prospective students. The study aims to identify the marketing strategies employed, evaluate their effectiveness, and recommend areas for improvement. A quantitative research design was utilised, surveying first-year students enrolled in private colleges to assess the impact of various marketing techniques. Purposive sampling was used to obtain 112 respondents who participated in the study and SPSS Version 29 and Microsoft Excel were used to analyse the collected data. Descriptive and inferential statistics were used to assess the effectiveness of the marketing strategies and identify trends. The findings reveal that print advertisements, word-of-mouth referrals and scholarships are the most influential marketing strategies. In contrast, methods like television commercials and online advertising show limited effectiveness. Recommendations include enhancing digital marketing efforts and refining personalised communication strategies to better engage prospective students. The study contributes to the understanding of marketing dynamics in the education sector and provides actionable insights for improving student recruitment practices
Thesis (MBA.) -- University of Limpopo, 2025
Keywords: Marketing strategies; Private colleges; Higher Education; Student perceptions; Recruitment; Marketing -- Management; Advertising; Private universities and colleges -- South Africa -- Limpopo; Education, Higher -- South Africa -- Limpopo; College students -- Recruiting -- South Africa -- Limpopo